Optimizing Community Policing through Strategic Communication and Trust Building in South Africa - John Motsamai Modise (Current Progress in Arts and Social Studies Research Vol. 9, 2025)
The purpose of this study is to investigate the variables affecting community policing forums and boards (CPF/CPBs) in South Africa in terms of efficacy. In particular, it looks into how buy-in from the police, community involvement, trust, and communication all contribute to the success of these cooperative systems. Principal subjects: The value of trust and communication in community policing, the function of CPFs and CPBs in promoting trust and communication, Opportunities and difficulties facing CPFs and CPBs, as well as variables affecting their efficacy. Key Arguments/Findings: Successful community policing depends on effective communication and trust, and CPFs and CPBs are critical in bridging the trust gap and fostering communication between the police and the community. Obstacles include limited resources, community involvement, and police support can reduce CPF/CPB efficacy. CPF/CPBs may greatly enhance public safety and fortify ties between the community and the police by tackling these issues and encouraging inclusive participation. Methodological approach: This study uses a qualitative approach that includes in-depth interviews with members of the CPF/CPB, community leaders, and police officers. To find important themes and patterns pertaining to the variables impacting CPF/CPB effectiveness, the obtained data is evaluated. Significance/Implications: Law enforcement groups, community organizations, and lawmakers should all take note of the research’s findings. Understanding the elements that make CPFs and CPBs successful can help develop strategies to improve their efficacy and advance more successful community policing in South Africa. Audience: Policymakers, law enforcement officers, community leaders, and academics with an interest in public safety and community policing are the main recipients of this research. In conclusion, community policing boards and forums are a viable strategy for enhancing public safety and fortifying ties between the community and the police in South Africa. Through the resolution of issues and the advancement of efficient communication, trust, police buy-in, and community participation, CPF/CPBs can make a substantial contribution to the development of more inclusive and safe communities.